Family Matters: Moving Beyond “If” Family Support Matters to “Why” Family Support Matters during Reentry from Prison - Mowen, Thomas J. (J Res Crime Delinq, 2018)
OBJECTIVES: Informed by social control and differential coercion and social support theories, we examine how multiple theoretically and methodologically distinct factors of family support relate to reincarceration, substance use, and criminal offending during prison reentry. METHOD: Using four waves of data from the Serious and Violent Offender Reentry Initiative, we identified three separate factors of family support—interactional (e.g., providing guidance and support), instrumental (e.g., providing housing and transportation), and emotional (e.g., providing love and belongingness). A series of mixed-effects models examined how each form of family support related to reincarceration, substance use, and criminal offending. RESULTS: Findings demonstrated that instrumental, but not interactional or emotional, support related to significantly lower odds of reincarceration and lower levels of substance use and criminal offending. Interaction terms revealed that the effect of instrumental family support is almost entirely independent, and not interactive, on each outcome. CONCLUSIONS: Family support appears to relate to prosocial reentry outcomes not because of emotional or interactional bonds, but because families provide for the basic needs of returning individuals. Instrumental familial support mechanisms such as providing housing and financial support appear more salient in promoting prosocial reentry outcomes than mechanisms of emotional or interactional support.